Pengembangan LKPD Berbasis Project Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis Siswa pada Materi Bioteknologi Konvesional Kelas XII SMA/IPA - Humayroh, Siti; Anas, Nirwana; Nina Adlini, Miza (Sci-tech Journal, 2023)
The research that has been carried out is entitled "Development of LKPD Based on Project Based Learning to Improve Students' Critical Thinking Skills in Biotechnology Material for Class problems, understanding assumptions, formulating and selecting relevant hypotheses. There are five indicators in developing critical thinking, namely; formulate the main problem, reveal existing facts, choose logical arguments, detect different points of view and draw conclusions. This research aims to improve students' critical thinking skills at DHARMAWANGSA MEDAN PRIVATE HIGH SCHOOL in Biology learning. Research Methodology uses Research and Development. The research population was class XII students at DHARMAWANGSA PRIVATE SMA with a sample size of 32 students. Data collection techniques use LKPD, observation sheets and documentation. Data analysis techniques use the level of validity, level of practicality and level of effectiveness. The research results showed that the Validity Level was 85.5% in the very strong category, the Practicality Level was 71.0% in the practical category and the Effectiveness Level was 56.6% in the quite practical category at DHARMAWANGSA MEDAN PRIVATE HIGH SCHOOL. Based on the research above, it can be concluded that the overall level of validity, level of practicality and level of effectiveness of students at DHARMAWANGSA MEDAN PRIVATE HIGH SCHOOL in biology learning is in the good category, although there are still skill aspects below the average percentage value. So this indicates that students are able to face challenges in students' critical thinking skills in the Project Based Learning model